2020
DOI: 10.3389/fneur.2019.01392
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnostic Models Between Vasovagal Syncope and Psychogenic Pseudosyncope in Children

Abstract: Objective: We aimed to establish useful models for the clinical differential diagnosis between vasovagal syncope (VVS) and psychogenic pseudosyncope (PPS). Methods: This bicentric study included 176 patients (150 VVS and 26 PPS cases) for model development. Based on the results of univariate and multivariate analyses, a logistic regression model and a scoring model were established and their abilities to differentiate VVS from PPS were tested. Another 78 patients (53 VVS and 25 PPS) were used for external vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Therefore, the results of this study will be helpful to suggest reasonable referrals and optimize the differential diagnostic process in clinical practice. Furthermore, compared with the previous study ( 24 ), this scoring model, for the first time, used the clinical manifestations only instead of doing a variety of laboratory investigations at the initial diagnostic step, and the newly developed scoring model yielded relatively high sensitivity and specificity for differentiating PPS from VVS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results of this study will be helpful to suggest reasonable referrals and optimize the differential diagnostic process in clinical practice. Furthermore, compared with the previous study ( 24 ), this scoring model, for the first time, used the clinical manifestations only instead of doing a variety of laboratory investigations at the initial diagnostic step, and the newly developed scoring model yielded relatively high sensitivity and specificity for differentiating PPS from VVS.…”
Section: Discussionmentioning
confidence: 99%
“…However, how to quantify these various clinical features and use them to discriminate between PPS and VVS is an urgent issue in clinical practice. In a previous study, the authors described a model composing of the posture during an episode, loss of consciousness (LOC) duration, and electrocardiogram-derived QT dispersion ( 24 ). However, the result of QT dispersion cannot be determined in a very quick and convenient way in grassroots hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that this method can be used to evaluate the function of cardiac autonomic nerve. Zhang et al [ 19 ] through the Logical regression model analysis of 176 patients (150 VVS patients and 26 cardiogenic pseudosyncope patients), the results showed that QTd, syncope duration and upright posture could distinguish VVS from psychogenic pseudosyncope, in which the area under the QTd curve was 0.892. Cardiogenic pseudosyncope usually had no autonomic nervous dysfunction, which further indicated that QTd could reflect cardiac autonomic nervous function.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 67 ] analyzed the clinical features of 150 children with VVS and 26 with pseudosyncope and established a scoring model that could differentiate between the 2 groups. This study evaluated clinical symptoms and ECG data and vital signs [ 67 ].…”
Section: Pediatric Application Of Syncope Diagnostic Scores Based On ...mentioning
confidence: 99%